1997
DOI: 10.1021/la960523d
|View full text |Cite
|
Sign up to set email alerts
|

Nanotribological Properties of Octadecyltrichlorosilane Self-Assembled Ultrathin Films Studied by Atomic Force Microscopy:  Contact and Tapping Modes

Abstract: Atomic force microscopy, working in contact and tapping modes, has been used to probe the mechanical response of octadecyltrichlorosilane, CH3−(CH2)17−SiCl3 (OTS), self-assembled ultrathin films grafted on silicon-treated surfaces. To assess the adhesion hysteresis and the elasticity of the films, we have performed loading and unloading experiments in contact mode. The effect of compression is observed while the load is being applied to the film. Once the load is fully removed, the film remains compressed show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Most data were fitted to DVLO theory with constant and dissimilar surface potential boundary conditions (20) and nonretarded van der Waals interaction (26). However, for hydrophobic interactions an additional acid-base (AB) attractive term was added (27), and the final expression for force normalized with the particle radius (F/R) in N/m is [8] where ε 0 is the permittivity of free space (C 2 /J m), κ is the reciprocal Debye length (m Interactions in deionized water. Results for experiments conducted in deionized water (pH ∼ 6) are presented graphically in Fig.…”
Section: Effect Of Surface Hydrophobicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most data were fitted to DVLO theory with constant and dissimilar surface potential boundary conditions (20) and nonretarded van der Waals interaction (26). However, for hydrophobic interactions an additional acid-base (AB) attractive term was added (27), and the final expression for force normalized with the particle radius (F/R) in N/m is [8] where ε 0 is the permittivity of free space (C 2 /J m), κ is the reciprocal Debye length (m Interactions in deionized water. Results for experiments conducted in deionized water (pH ∼ 6) are presented graphically in Fig.…”
Section: Effect Of Surface Hydrophobicitymentioning
confidence: 99%
“…Garcia-Parajo et al (8) assessed the adhesion hysteresis and the elasticity of thin films of octadecyltrichlorosilane (OTS) grafted on silicon-treated surfaces. They performed loading and unloading experiments and verified that the film exhibited viscoelasticity, with relaxation times in the range of 0.1 s. Feldman et al (9) measured pull-off forces between a series of polymer films and spherical probes (glass and polystyrene).…”
Section: Introductionmentioning
confidence: 99%
“…70 However, the authors found the OTS SAMs instantly breakdown and failed under a higher load of 1 N. Garcia-Parajo et al studied OTS SAMs on silicon with force distance curves and compressive forces, and proposed that rearrangement of OTS under compression and the subsequent reformation aer load was removed contributes to the lubricity of OTS SAMs. 165 Flater et al demonstrated that OTS SAMs can reduce adhesion of silicon wafers through pull off measurements using AFM, and also noticed that friction is reduced further when OTS SAMs are created on both the cantilever and substrate. 164 Inuence of chain length and head group.…”
Section: 147mentioning
confidence: 99%
“…It has been reported that SAM could be damaged at a pressure of \1 GPa at the nano-scale [46,47]. However, the critical pressure at which SAM is destroyed is difficult to assess since it varies according to the contact area and also because SAM layer includes defects or disorders that are hard to characterize [48][49][50]. When the contact area increases, the number of defects or disorders involved in the force interaction is likely to increase as well.…”
Section: Wear Characteristics On Ots-sam Coated Silicon Surfacementioning
confidence: 99%